How GRAIL controls Treg function to maintain self-tolerance - Fathman, C. Garrison; Yip, Linda; Gómez-Martín, Diana; Yu, Mang; Seroogy, Christine M.; Hurt, Clarence R.; Lin, Jack T.; Jenks, Jennifer A.; Nadeau, Kari C.; Soares, Luis (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) normally maintain self-tolerance. Tregs recognize “self” such that when they are not working properly, such as in autoimmunity, the immune system can attack and destroy one’s own tissues. Current therapies for autoimmunity rely on relatively ineffective and too often toxic therapies to “treat” the destructive inflammation. Restoring defective endogenous immune regulation (self-tolerance) would represent a paradigm shift in the therapy of these diseases. One recent approach to restore self-tolerance is to use “low dose IL-2” as a therapy to increase the number of circulating Tregs. However, studies to-date have not demonstrated that low-dose IL-2 therapy can restore concomitant Treg function, and phase 2 studies in low dose IL-2 treated patients with autoimmune diseases have failed to demonstrate significant clinical benefit. We hypothesize that the defect in self-tolerance seen in autoimmunity is not due to an insufficient number of available Tregs, but rather, due to defects in second messengers downstream of the IL-2R that normally control Treg function and stability. Previous studies from our lab and others have demonstrated that GRAIL (a ubiquitin E3 ligase) is important in Treg function. GRAIL expression is markedly diminished in Tregs from patients with autoimmune diseases and allergic asthma and is also diminished in Tregs of mice that are considered autoimmune prone. In the relevant pathway in Tregs, GRAIL normally blocks cullin ring ligase activity, which inhibits IL-2R desensitization in Tregs and consequently promotes Treg function. As a result of this defect in GRAIL expression, the Tregs of patients with autoimmune diseases and allergic asthma degrade IL-2R-associated pJAK1 following activation with low dose IL-2, and thus cannot maintain pSTAT5 expression. pSTAT5 controls the transcription of genes required for Treg function. Additionally, the GRAIL-mediated defect may also allow the degradation of the mTOR inhibitor, DEP domain-containing mTOR interacting protein (Deptor). This can lead to IL-2R activation of mTOR and loss of Treg stability in autoimmune patients. Using a monoclonal antibody to the remnant di-glycine tag on ubiquitinated proteins after trypsin digestion, we identified a protein that was ubiquitinated by GRAIL that is important in Treg function, cullin5. Our data demonstrate that GRAIL acts a negative regulator of IL-2R desensitization by ubiquitinating a lysine on cullin5 that must be neddylated to allow cullin5 cullin ring ligase activity. We hypothesize that a neddylation inhibitor in combination with low dose IL-2 activation could be used to substitute for GRAIL and restore Treg function and stability in the Tregs of autoimmune and allergic asthma patients. However, the neddylation activating enzyme inhibitors (NAEi) are toxic when given systemically. By generating a protein drug conjugate (PDC) consisting of a NAEi bound, via cleavable linkers, to a fusion protein of murine IL-2 (to target the drug to Tregs), we were able to use 1000-fold less of the neddylation inhibitor drug than the amount required for therapeutically effective systemic delivery. The PDC was effective in blocking the onset or the progression of disease in several mouse models of autoimmunity (type 1 diabetes, systemic lupus erythematosus, and multiple sclerosis) and a mouse model of allergic asthma in the absence of detectable toxicity. This PDC strategy represents targeted drug delivery at its best where the defect causing the disease was identified, a drug was designed and developed to correct the defect, and the drug was targeted and delivered only to cells that needed it, maximizing safety and efficacy.